The wounded self - Schmidt, Nina (Camden House, 2018)
In the German-speaking world there has been a new wave - intensifying since 2007 - of autobiographically inspired writing on illness and disability, death and dying. Nina Schmidt's book takes such writing seriously as literature, examining how the authors of such personal narratives come to write of their experiences between the poles of cliché and exceptionality. Identifying shortcomings in the approaches taken thus far to such texts, she makes suggestions as to how to better read such narratives from the stance of literary scholarship, then demonstrates the value of a literary disability studies approach to such writing with close readings of Charlotte Roche's Schoßgebete (2011), Kathrin Schmidt's Du stirbst nicht (2009), Verena Stefan's Fremdschläfer (2007), and - in the final, comparative chapter - Christoph Schlingensief's So schön wie hier kanns im Himmel gar nicht sein! Tagebuch einer Krebserkrankung (2009) and Wolfgang Herrndorf's blog-cum-book Arbeit und Struktur (2010-13). Schmidt shows that authors dealing with illness and disability do so with an awareness of their precarious subject position in the public eye, a position they negotiate creatively. Writing the liminal experience of serious illness along the borders of genre, moving between fictional and autobiographical modes, they carve out spaces from which they speak up and share their personal stories in the realm of literature, to political ends. Nina Schmidt is a postdoctoral researcher in the Friedrich Schlegel School of Literary Studies at the Freie Universität Berlin.
Title from publisher's bibliographic system (viewed on 02 Aug 2018)
Keywords: Deutsch; Literatur; Krankheit; Behinderung; Sterben; Tod; Autobiografische Literatur